Women’s Participation and Representation in Local Government: The Case of Yilo Krobo and Ga East Municipalities Between 2009 and 2021 - Appiah, D.O.Y. (University of Ghana, 2023)
This study examined women’s participation and representation in local government of two municipal assemblies in Ghana, Yilo Krobo and Ga East. The persistent under-representation and low participation of women in local government has attracted worldwide debate and concerns. Globally, women are less represented in position of power at both national and local levels. Most countries in Africa, including Ghana, have very few women in position of power at both national and local levels. The objectives of the study were to assess the trends in participation and representation in local government between the two municipalities between 2009 and 2021, account for the low participation and representation of women in local government and highlight the contributions of political parties and local government authorities in the promotion of women’s participation and representation in local government. The method employed to carry out the objectives of the study was qualitative. The methodology effectively involved secondary data and obtained valuable insights from 24 primary respondents through the use of Key Informant Interviews (KII) and Focus Group Discussions (FGD). The study discovered that, there were significantly low representation of women in local government in both Yilo Krobo and Ga East municipalities despite efforts to advance women’s involvement in politics. The study also found that women’s participation in voter registration and turnout was somewhat better than women’s nomination in elections or elected positions. Furthermore, the study discovered that barriers to women’s involvement and representation in local government and politics include inadequate financial resources, low levels of education, gender prejudices, lack of support from spouses, lack of self-confidence, and reproductive duties. The study also found that political parties and municipal government supported women’s public engagement although not to a greater degree. The study also makes recommendations to increase women’s participation and representation in the political space. Firstly, it suggests that financial support be made available to female candidates to enhance their capacity to compete effectively in elections. Additionally, provide educational scholarships for women to enhance their academic qualifications to enabling them to compete on equal footing with male counterparts. Moreover, undertake public education with a focus on gender bias to foster inclusive political environments that accommodate both genders. Lastly, implement and enforce quotas and affirmative actions to ensure gender parity in local governance and national polity at large.
MA. Development Studies
Keywords: Ghana; Yilo Krobo; Ga East; women